"I'm Pleased with My Body": Older Men's Perceptions and Experiences of Their Aging Bodies. (June 2021) - Hurd, Laura; Mahal, Raveena
To date, the body image literature has largely ignored older men, as the bulk of the research has focused on young and middle-aged women. Where studies have been conducted with older men, they have tended to only consider the perspectives of men in their 50s and 60s or to include older men as part of mixed gender or diverse age samples. Thus, little is known about how older men perceive, experience, and feel about their aging and changing bodies, even as the body is central to older men's understanding and practice of masculinity as well as their position in age- and gender-based systems of inequality. Addressing this gap in the research, we conducted in-depth interviews with 22 community-dwelling men aged 67–90 years (average age of 77 years). Drawing upon age relations and masculinities theorizing, we asked the men about how they evaluated and felt about their appearances, health, physical abilities, and sexual functioning. Our thematic analysis revealed that the men were largely satisfied with their appearances and physical functioning, particularly their approximation to masculine ideals of youthfulness, healthiness, and independence. Whereas half of the men identified their weight as a source of body satisfaction, all of the men disparaged obesity and stereotypical older men's enlarged stomachs in particular. That said, the men discounted appearance as an unimportant and feminized concern. In contrast, they emphasized the salience of health and body functionality, expressing concern about how changes to their physical abilities and sexual functioning had already affected, and might in the future increasingly delimit, their daily lives, and hence they preferred social and physical pursuits. We consider our findings in light of age and masculinity ideals, which collectively privilege youthful bodies and subordinate older men.